PENGARUH PENGGUNAAN E-MODUL MATEMATIKA BERBASIS CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI PESERTA DIDIK KELAS X SMKN 1 SIJUNJUNG - Anwar, Fahrezi (Jurnal Edukasi dan Penelitian Matematika, 2024)
Improving their numerical literacy is one of the goals that the pupils are working towards. However, this is still an area where the students in SMKN 1 Sijunjung's class X fall short. This problem can be solved by using e-modules that incorporate contextual learning and teaching strategies. This study aims to compare the numeracy literacy of students who get direct instruction using school-provided teaching materials to that of students whose education is supplemented with e-modules based on content-based learning (CTL). Using a research strategy called the nonequivalent post test-only control group design, the study employed a quasi-experimental research approach. Students in the X grade at SMKN 1 Sijunjung were part in this research. There were two classes that participated in the study: X Accounting 2 and X Accounting 1. The former class employed CTL-based e-modules as a treatment, while the latter class used school-provided teaching materials for direct learning. The data analysis led the author to the conclusion that CTL-based e-modules improve students' numeracy literacy skills in class X at SMKN 1 Sijunjung compared to classes that depend on school-provided learning and teaching materials. These results show that students who use e-modules based on CTL have better numeracy literacy abilities.Keywords– Numeracy Literacy Skills, E-Module, Contextual Teaching and Learning